2020
DOI: 10.1152/advan.00141.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Wright table of the cardiac cycle: a stand-alone supplement to the Wiggers diagram

Abstract: The Wright table is introduced as a novel tool for teaching and learning the cardiac cycle. It supplements the nearly 100-yr-old Wiggers diagram, which is information rich but difficult for many students to learn. The Wright table offers a compact presentation of information, viewable both in terms of how 1) each compartment’s pressures and flows change over time; and 2) the heart works as a pump, first filling and then emptying the ventricles, thereby moving blood from low-pressure venous to high-pressure art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Nonetheless, all three pcECM formulations performed very well under burst testing compared to pressures they would be exposed to in vivo. Central venous pressures of healthy individuals typically range from 0 to 6 mmHg [43][44][45] over one cardiac cycle and can increase 20-30 mmHg in patients undergoing heart failure. 46 All three pcECM formulations withstood pressure at least 10 times greater than pressures typically observed within the VC under any condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, all three pcECM formulations performed very well under burst testing compared to pressures they would be exposed to in vivo. Central venous pressures of healthy individuals typically range from 0 to 6 mmHg [43][44][45] over one cardiac cycle and can increase 20-30 mmHg in patients undergoing heart failure. 46 All three pcECM formulations withstood pressure at least 10 times greater than pressures typically observed within the VC under any condition.…”
Section: Discussionmentioning
confidence: 99%
“…46 All three pcECM formulations withstood pressure at least 10 times greater than pressures typically observed within the VC under any condition. Additionally, systolic pressure in the aorta typically ranges from ≤120 mmHg 43 in healthy individuals to ≤180 mmHg under severe hypertension. 47 Burst strength experiments in this study showed that the low and medium crosslinking density pcECM formulations could withstand the highest arterial pressures even under hypertension, suggesting these formulations could be suitable for arterial hemorrhage applications as well.…”
Section: Discussionmentioning
confidence: 99%
“…For the simulation of sinus rhythm conditions, a uniformly distributed pressure was applied at the open surface of the fluid, based on the physiological atrial pressure described in the Wiggers diagram ( 37 , 38 ). Then, as described above, a virtual change of temperature was applied to the structure to simulate active contraction (see Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%